Player turnover and team performance in FIFA Women's World Cup - Júlia Barreira; Gabriela Carvalho de Sousa; Larissa Rafaela Galatti
Abstract Aims: The specific aims of this study were to characterize player turnover on FIFA Women's World Cup (1991-2015), and to explore the relationship between the turnover rate and team performance. Methods: We analyzed the seven national teams that participated in all of the seasons of the women's World Cup: Brazil, Germany, Japan, Nigeria, Norway, Sweden, and the USA. The full name of the players was used to analyze which athlete was maintained or substituted from a season to another. The names of the players were retrieved from the official FIFA website. Player turnover was measured by the percentage of players that were on a team in one season and were not on the roster on the following edition. The performance was measured by the final classification of the teams. Results: The results showed that most players participated only in one season of the championship. An average rate of 53% of player turnover per team was found by edition, which represents, approximately, 13 substituted athletes. Medalist teams showed lower player turnover (48%) compared to the non-medalist teams (57%) (p-value=0.0305; ES=0.69). Furthermore, teams that were classified for the quarterfinals decreased player turnover in the next season (p-value=0.0408, ES=0.89), maintaining a good performance (χ²=4.114, p-value=0.042). We could not find any influence of higher turnover rates on team performance (χ²=0.535, p-value=0.464). Conclusion: The present study found that lower rates of player turnover may be beneficial for team performance in the FIFA Women's World Cup. When successful teams decrease their turnover rate, sports performance seems to be maintained.